Elements of young adult literature in texts used in Malaysian secondary schools - Mukundan, Jayakaran; Govindarajoo, Mallika V. (Australian International Academic Centre, 2013)
This article presents the results of a study to determine the extent to which the themes, issues and portrayal of young adult characters in the novels used in the Malaysian secondary school English Language classroom fulfilled the criteria of Young Adult Literature (YAL). The novels studied were Step by Wicked Step (A.Fine, 1996), Catch us if You Can (K. McPhail, 2004) and The Curse ( S.A. Lee, 2010). Sampling was purposeful and data came from participants’ journal reflections and qualitative interviews. The findings showed that the themes in all three novels complied to the general list of themes common to YAL with family relationships and determination being the most prominent. The depiction of an adolescent protagonist who is strong and perceptive is evident in all three novels. However the young adult protagonist’s voice, conflict between dependence and independence and the journey towards maturing characteristic of YAL is only distinct in Step by Wicked Step and Catch us if You Can. Description of the young adult protagonists’ appearance and mannerisms was also limited in all the novels.